1996
DOI: 10.1001/archpsyc.1996.01830100061008
|View full text |Cite
|
Sign up to set email alerts
|

Treating Major Depression in Primary Care Practice

Abstract: Pharmacotherapy and psychotherapy effectively treat major depression among primary care patients when provided within specific parameters and for the full acute and continuation phases. Treatment principles recommended by the Depression Guideline Panel of the Agency for Health Care Policy and Research are supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(111 citation statements)
references
References 37 publications
2
97
0
4
Order By: Relevance
“…Despite a substantial literature on depression in the primary care setting, and strong evidence supporting the AHCPR depression treatment guidelines [43], it is possible that the information and recommendations put forth have not found their way to PCPs at large. Indeed, Feldman et al [44]surveyed 992 family physicians and found that only one third were aware of the AHCPR depression guidelines, and only 13% had a copy of the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a substantial literature on depression in the primary care setting, and strong evidence supporting the AHCPR depression treatment guidelines [43], it is possible that the information and recommendations put forth have not found their way to PCPs at large. Indeed, Feldman et al [44]surveyed 992 family physicians and found that only one third were aware of the AHCPR depression guidelines, and only 13% had a copy of the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Unter denen, die als depressiver "Fall" erkannt wurden, erhält nur ein Bruchteil eine Behandlung, die gemäß fachlicher Leitlinien als adäquat bezeichnet werden kann. Dabei wird speziell im deutschen Sprachraum auf die vergleichsweise hohen Raten von Sedativa-Verschreibungen, sowie die im Vergleich zu trizyklischen Antidepressiva niedrigeren Verschreibungsraten an SSRIs hingewiesen [2,5,7,16].…”
Section: Schlüsselwörterunclassified
“…Numerous statistical reworkings of this landmark study have done little to change the outcome pattern (Gibbons et al, 1993;Klein & Ross, 1993). Schulberg et al (1996Schulberg et al ( , 1998 also reported a more rapid and effective outcome for IPT compared with GP treatment as usual in primary care patients with depression but found that initial severity of depression and functional ability were unrelated to clinical course.…”
Section: Evidence Basementioning
confidence: 97%